Gender Phonology Studies: Differentiating Male & Female Voices through Praat Acoustic Analysis - Batubara, Nisa Anggraini; Rajagukguk, Desy Lampita; Rohani Ganie, Rohani Ganie; Maharani, Puan (TALENTA, 2025)
This study aims to (1) find out the differences in the frequency of male and female voice of Toba Bataknese Native Speakers, (2) to know how the difference between male and female voice duration of Toba Bataknese Native Speakers, (3) to know how the difference of male and female voice intensity of Toba Bataknese Native Speakers. This research uses instrumental approach, that is using a computer with application of Praat program. The population in this study were male voice and adult female voice of Toba Bataknese Native Speakers. The sample in this research is taken from the voice of 1 man and the voice of 1 woman of Toba Bataknese Native Speakers. The results of this study show that (1) the initial frequency of men is smaller than the female’s initial frequency, the final frequency of the male is smaller than the female final frequency, the male’s highest frequency is smaller than the female high frequency, male is smaller than the lowest female frequency. In general, it can be said that the male voice frequency is smaller than the female voice frequency. (2) The duration of the male voice is shorter than the duration of the female voice. (3) The male’s initial intensity is smaller than the female’s initial intensity, the male’s final intensity is greater than the female’s final intensity, the male’s highest intensity is smaller than the intensity of the female’s, the male’s lowest intensity is greater than at the lowest intensity of women.